The research change in Iranian family intimacy and personal relationships - ماریا رحیمی; محمد رضایی (مطالعات زن و خانواده, 2017)
In this study,The qualitative research method and Grounded Theory approach to the study of personal relationships and intimacy and affection in the Iranian family ties in the past three decades;The population of Iranian students past three decades.Among the findings of this Study can be increased individualism in personal interactions during the evolution noted And as the most important finding of this research can be used to change the position of interactions with friends and colleagues as a new channel on people's personal relationships. The border between relatives and non-relatives disappeared in Iranian family. The configuration change Iranian family, gender had a significant impact The change in the social status of women, as well as the use of virtual communication,A more intimate relationship than men with their friends and colleagues and has had an important role in this transformation.Keywords: personal relationships, intimate relationships, family interactions, family configuration, evolution of the family